Virtual shelves in a digital library: a framework for access to networked information sources. - Patrick TB; Springer GK; Mitchell JA; Sievert ME; Patrick, T B; Springer, G K; Mitchell, J A; Sievert, M E (Journal of the American Medical Informatics Association, 1995)
Objective: Develop a framework for collections-based access to networked information sources that addresses the problem of location-dependent access to information sources.Design: This framework uses a metaphor of a virtual shelf. A virtual shelf is a general-purpose server that is dedicated to a particular information subject class. The identifier of one of these servers identifies its subject class. Location-independent call numbers are assigned to information sources. Call numbers are based on standard vocabulary codes. The call numbers are first mapped to the location-independent identifiers of virtual shelves. When access to an information resource is required, a location directory provides a second mapping of these location-independent server identifiers to actual network locations.Results: The framework has been implemented in two different systems. One system is based on the Open System Foundation/Distributed Computing Environment and the other is based on the World Wide Web.Conclusions: This framework applies in new ways traditional methods of library classification and cataloging. It is compatible with two traditional styles of selecting information searching and browsing. Traditional methods may be combined with new paradigms of information searching that will be able to take advantage of the special properties of digital information. Cooperation between the library-informational science community and the informatics community can provide a means for a continuing application of the knowledge and techniques of library science to the new problems of networked information sources.